Indirect dark matter searches in ultra faint dwarf galaxies - Kherlakian, Maria Carolina (2020)
The nature of dark matter is still one of the biggest mysteries of modern cosmology. Unveiling its complexion through indirect observations of gamma-rays requires state of the art observatories, such as the Cherenkov Telescope Array (CTA). The Milky Way satellites constitute a promising target for the search of Weakly Interacting Massive Particles (WIMPs) via indirect searches due to their low astrophysical background. However, the overall census of the dark matter galactic substructures is incomplete. This is owing to the sky coverage and sensitivity limitations of sky-survey experiments. Moreover, N-body simulations indicate that a much higher number of satellites should exist. In this work we present a modelling of the galactic sub-clumps based on statistical estimations of the full Milky Way satellite population. We introduce 10 substructure modellings (SMi, i ∈ {1, . . . , 10}) with the following varying parameters: the substructure inner dark matter profile, its mass and radial distribution around the Milky Way, the expected number of satellites given by various studies and the mass-concentration relation. We simulate hundreds of skymaps with the CLUMPY code based on the sub-halo modellings. We show that the mass-concentration parametrization and the predicted number of sub-halos handed over the most substantial effects on the source J-factor. The sources are then used to investigate the detectability of sub-halos with the CTA. We assume two cases: if a dark matter signal is seen by the CTA or if there is no detection. For both we calculate the sensitivity curves of sources resolved in the simulations for the τ+τ- and bb channels. In general, the τ+τ- channel maintained the most constrained sensitivity curves. There was no substantial difference on the sensitivity curve for sources placed on the north and south hemisphere. In the case of detection of a signal with the CTA, no model was effective to access the thermal values of {σv}. In case of no signal observation, only the model with the highest median J-factcor could probe the thermal values of {σv}.